COMMUNI.CARE (COMMUNIcation and Patient Engagement at Diagnosis of PAncreatic CAncer): Study Protocol - Consolandi, Monica; Martini, Carlo; Reni, Michele; Arcidiacono, Paolo Giorgio; Falconi, Massimo; Graffigna, Guendalina; Capurso, Gabriele (Frontiers in Medicine, 2020)
BACKGROUND: The diagnosis of pancreatic adenocarcinoma (PDAC) in many cases is completely unforeseen by the patient, who often faces a disease that is already at an advanced stage, with poor prognosis. The clinical visit during which the diagnosis is communicated together with the first information regarding the planned treatments is of paramount importance. We hypothesize that the clarity of such information is able to influence patients’s engagement and thus the compliance. AIMS: The aim of this study is to collect quantitative data on the level of PDAC patient engagement and the rate of understanding of the information received from the doctor, and investigate the possible association between these two variables and with the patient's level of compliance. METHODS: This is a single-center, observational, cross-sectional cohort study focused on patients diagnosed with PDAC, approved by the Ethics Committee of the San Raffaele Hospital. As no preliminary data are available on the association between PDAC patient's understanding rate and their level of engagement and of compliance no power calculation is possible. This is a pilot study, aimed at enrolling at least 45 PDAC patients during a 3 months frame. CONCLUSION: COMMUNI.CARE will be the first study specifically investigating whether there is a relation between PDAC patients’ rate of understanding, their engagement and compliance at time of diagnosis.